2016
DOI: 10.1002/pds.3946
|View full text |Cite
|
Sign up to set email alerts
|

Association between knowledge about levonorgestrel emergency contraception and the risk of ectopic pregnancy following levonorgestrel emergency contraception failure: a comparative survey

Abstract: ObjectiveTo study the association between knowledge about levonorgestrel emergency contraception (LNG‐EC) and the risk of ectopic pregnancy (EP) following LNG‐EC failure.MethodsThis study included 600 women who had visited the hospital with LNG‐EC failure. Of these, 300 with EP and 300 with intrauterine pregnancy (IUP) were recruited to the EP group and IUP group respectively. The participants were interviewed face‐to‐face using a standardized questionnaire.Main Outcome MeasuresPearson's chi‐square tests and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…However, there could be women who use it without strictly adhering to the guidelines [3, 18]. Studies done in china showed 5 and 4 times increased odds of developing ectopic pregnancy in those who had used Levonorgestrel emergency contraceptive pill compared to non-users respectively [12, 13]. Although the use of Levonorgestrel only pills for emergency contraception significantly influenced occurrence of ectopic pregnancy (p < 0.001) among the cases; the findings of this study clearly indicate that occurrence of ectopic pregnancy could also be influenced by the use of other contraceptives such as depo Provera (< 0.001).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, there could be women who use it without strictly adhering to the guidelines [3, 18]. Studies done in china showed 5 and 4 times increased odds of developing ectopic pregnancy in those who had used Levonorgestrel emergency contraceptive pill compared to non-users respectively [12, 13]. Although the use of Levonorgestrel only pills for emergency contraception significantly influenced occurrence of ectopic pregnancy (p < 0.001) among the cases; the findings of this study clearly indicate that occurrence of ectopic pregnancy could also be influenced by the use of other contraceptives such as depo Provera (< 0.001).…”
Section: Discussionmentioning
confidence: 99%
“…However, most studies on contraception failure and pregnancy as the primary endpoint; did not report whether pregnancies following LNG-EC failure were intrauterine or extra-uterine [11]. Ectopic pregnancy is one of the causes of maternal morbidity and mortality in sub-Saharan Africa [12]. The incidence of ectopic pregnancy in Western Kenya continues to be a major cause of admission in health facilities [13].…”
Section: Introductionmentioning
confidence: 99%
“…In general, Chlamydia infection, which is one of the most common risk factors for an ectopic pregnancy, also decreases ciliary movement and causes tubal damage. Although it was reported that a previous C. trachomatis infection, detected with a serum C. trachomatis immunoglobulin G test, was not greater in those who had an ectopic pregnancy compared with those who had an intrauterine pregnancy following LNG‐EC failure, other factors including incorrect emergency contraception use might affect these results . In any case, repeat testing for reinfection of C. trachomatis should be recommended .…”
Section: Discussionmentioning
confidence: 99%
“…113 A study found that among women with LNG-EC failure, the primary sources of information included friends, TV, and the Internet. 114 Social networks, including family, friends, and media, were shown to be important for the contraceptive decision-making in African American and Latina women. 115 An analysis of information on EC using a Google search in April 2020 found that the information showed low credibility overall and many web sites were too complex for regular consumers.…”
Section: Areas Of Uncertaintymentioning
confidence: 99%